Fertility and Pregnancy Outcomes After Conservative Management of Adenocarcinoma In Situ of the Cervix. Issue 4 (October 2021) - Bell, Sarah G.; Peng, Katie; Kobernik, Emily K.; Miller, Madison E.; Lieberman, Richard; Saunders, Natalie A.; Welch, Kathryn C.; Campbell, Elizabeth J.
Abstract : Objective: The aim of the study was to evaluate the pregnancy outcomes of women who underwent conservative management of adenocarcinoma in situ (AIS). Materials and Methods: We conducted a retrospective chart review of patients diagnosed with AIS at a single tertiary institution between January 1, 1991, and December 31, 2019. We collected demographic data, AIS-specific information, and fertility outcomes and performed bivariate analyses to compare demographic characteristics and AIS-specific information between patients with and without hysterectomy after diagnosis. Patients with conservative management who achieved pregnancy were described. Results: Among 87 patients with AIS, 38 (44%) underwent a hysterectomy within 6 months of diagnosis and 49 (56%) underwent conservative management. Six of 19 patients (32%) had residual AIS despite undergoing definitive management after an excisional procedure with negative margins and negative endocervical curettage (ECC). Nine of 19 patients (47%) had residual AIS after an excisional procedure with positive margins and/or a positive ECC. Patients who opted for conservative management were younger (median = 31.6 [interquartile range = 27.4–34.9] vs 38.5 y [32.3–44.8 y], p < .001) and nulligravid. Among patients with conservative management, there were 15 pregnancies and 14 live births (29%). Seven were preterm, although 2 were for medical indications. Conclusions: Residual AIS in patients with negative margins and ECC leading to definitive hysterectomy (32%) and the rate of preterm birth (36%) were higher than previous reports and nationally reported rates. However, only 1 patient had a preterm birth before 34 weeks. These findings reflect important information for counseling patients who elect for conservative management of AIS.